Key technologies of satellite communications aided by reconfigurable holographic surfaces - Xinyuan HU; Ruoqi DENG; Boya DI; Hongliang ZHANG; Lingyang SONG (Dianxin kexue)
Ultra-dense low earth orbit (LEO) satellite communication networks can overcome the scarcity of spectrum resources and the limited coverage of traditional terrestrial networks, and thus have the potential to provide high data rate services and global massive connectivity for terrestrial users.However, due to the high mobility of the satellites, LEO satellite networks put more stringent requirements on antenna technologies in terms of accurate beam steering and high antenna gain.Reconfigurable holographic surface (RHS), as a new type of metamaterial antenna, is investigated to assist LEO satellite communications.The RHS can electronically control the metamaterial units by leveraging the holographic principle to generate desired directional beams.Based on the hardware structure and holographic working principle of RHS, an RHS-assisted multi-satellite communication scheme was proposed, which considered both the LEO satellite tracking scheme and the data transmission scheme.A holographic beamforming optimization algorithm was also designed to maximize the sum rate.Simulation results verify the effectiveness of the proposed scheme and demonstrat that the RHS provids a more cost-effective way to support satellite communications than the conventional phased array antennas.